Prefixed Denominal Verbs in Indonesian Children's Story - Sotyarani Padmarintan; Tri Mastoyo Jati Kesuma (Universitas Islam Negeri Palopo, 2026)
This study aims to describe the prefixes that form denominal verbs and their meanings in Indonesian children's storybooks. Previous research tends to be general and less focused on children's production. This study examines prefixes and their meanings to describe the extent to which junior high school children master denominal verbs. With a descriptive qualitative approach, the research data in the form of sentences with denominal verb predicates are taken from the anthology Jangan Pernah Menyerah Wujudkan Mimpimu by junior high school students. The listening and note-taking methods were used for data collection, while the direct element division and paraphrasing techniques were used for affix and meaning analysis. The results show that junior high school students are able to produce denominal verbs with various prefixes. The prefix